QUALITY OF LIFE EVALUATION AND ASSOCIATED FACTORSIN ASTHMATIC CHILDREN AND ADOLESCENTS ATTENDED IN A SPECIALIZED OUTPATIENT CLINIC - Fernanda Chedid de Souza Fontan; Sérgio Wilson Duwe; Karoliny dos Santos; Jane da Silva (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To evaluate the quality of life and its association with disease control, severity, allergic comorbidities and adherence to treatment in children and adolescents with asthma. Methods: A cross-sectional study that included children and adolescents aged seven to 17. The Paediatric Asthma Quality of Life Questionnaire (PAQLQ) was used to assess their quality of life. Sociodemographic and clinical data were obtained from the chart and from a questionnaire. Descriptive statistics were performed and chi-square or Fisher's exact tests were used to verify the existence of associations between quality of life and disease control, severity, comorbidities and adherence to treatment. The level of statistical significance was set at p<0.05. Results: 101 children/adolescents were evaluated (62.4% boys), with a mean age of 10.1 years. On average, the PAQLQ score was ≤5.9 points, indicating moderate / severe quality of life impairment. Higher levels of control, as well as higher disease severity, were associated with higher quality of life impairment, both in total PAQLQ score and domains (p<0.05). The presence of comorbidities was also associated with higher quality of life impairment (p=0.01), except in the emotional function domain. Adherence to treatment showed no association with quality of life. Conclusions: Children and adolescents with asthma present impairment in their quality of life, and this is related to poorer control and severity of the disease, as well as to the presence of allergic comorbidities.